Análisis de la evolución, desafíos y logros en la inclusión educativa en Colombia (Memorias Sifored - Encuentros Educación UAN, 2023)
The community becomes the horizon of understanding of authentic educational processes, and the natural space of inclusive experience. Pedagogy is considered as a key element in the development of positive attitudes towards students in the implementation of inclusive education, it is essential that teachers show positive attitudes that favor inclusion in general. Exclusion is characterized by the systematic attitude of excluding certain people, for some particular circumstance, causing harm to them, and denying the social group the participation of all. Inclusion, on the other hand, refers to the reception of such persons in particular circumstances, but under conditions of equity. Its influence is manifested in social stereotypes, in expectations towards students, in study conditions, in family support and in the internalization of the pedagogy of those teachers with possibilities to continue educating students. At the same time, the analysis presented here allows the academic community, especially education professionals, to glimpse the progress and challenges in the area of inclusion, for which interdisciplinary and transdisciplinary work is essential. For this reason, given the need to understand the complexity of inclusive education and the linkage of the community, the main objective of this analysis is to identify the approach that is being given to inclusive education, in order to generate a critical reflective attitude in the educator, which can generate changes to promote institutional processes in favor of diversity. Research on educational inclusion has gained great importance in recent years. In this process, it is im- portant to review research on the implementation of the public policy of inclusion from the point of view of educational management.
Keywords: inclusion; exclusion; education; pedadogy; society; awareness